Translation of Reovirus Messenger RNAs Synthesized In Vitro into Reovirus Polypeptides by Several Mammalian Cell-Free Extracts - McDowell, Maxson J. (1972)
Single-stranded reovirus RNA, synthesized in vitro by reovirus cores, functioned as messenger RNA in cell-free extracts prepared from several mammalian cells: Krebs II mouse ascites cells, mouse L cells, Chinese hamster ovary cells, HeLa cells, and rabbit reticulocytes. As shown by acrylamide gel electrophoresis, all eight polypeptides known to be specified by reovirus were synthesized in the reticulocyte system. In the other extracts, from 5 to 7 complete virus proteins were made.